Kajian Karakteristik Spasial Dan Nonspasial Pengguna Ojek Daring Di Kawasan Pendidikan Tinggi Tembalang - Puspita Dhian Nusa; Okto Risdianto Manullang (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Technological developments are increasing from time to time and impact on all fields of life, including transportation. One of the online transportation services is online motorcycle that provides services for service users on a door to door basis. These conditions change people's travel behavior from public transportation to online transportation. The purpose of this study is to examine the variables of spatial and non-spatial characteristics that have a significant effect on the frequency of online transportation use. The research approach used is quantitative and analytical tools in the form of cross tabulation. The results of the study show that the spatial variable that is considered in determining the frequency of online transportation use is the distance of residence to local facilities. In addition, non-racial variables that have a relationship with the frequency of online transportation use are gender, age structure, motor vehicle ownership and income. The proposal is based on the results of research, related to the issue of online transportation in terms of online transportation users, the majority of whom are women, namely the need for additional features related to vehicle location, the identity of the driver who is forwarded to the family at home to ensure the safety of service users.